Hospital Management Information System Implementation Strategy ToImprove The Quality Of Health Services At Pindad General HospitalBandung - Fikri Emsa Silmi (Politeknik Mardira Indonesia, 2026)
The implementation of a Hospital Mahe Hospital Management Information System (SIMRS) is a critically strategic component in improving thequality of healthcare services. This study aims to examine the implementation of SIMRS, ident ify barriers to itsimplementation, and formulate effective implementation strategies at Pindad General Hospital (RSU Pindad), BandungCity. The research employed a descriptive qualitative approach using a single case study method. Data were collectedthrough in-depth interviews, direct observation, and document analysis from relevant stakeholders at RSU PindadBandung. Data analysis utilized SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) based on four SIMRSpillars: technoware, humanware, infoware, and organiware. The results indicate that SIMRS implementation at RSUPindad Bandung is suboptimal, as evidenced by a weakness score (1.82) exceeding the strength score (1.57) in the IFASmatrix, although opportunities (1.50) outweigh threats (1.30) in the EFAS matrix. This positions RSU Pindad in QuadrantIII (turn-around/WO strategy), indicating that the hospital must address internal weaknesses in order to leverage externalopportunities. Key barriers include limited IT human resources, an insuff icient SIMRS budget, the absence ofcomprehensive SOPs, and incomplete system adoption across units. The recommended strategies encompass four 4Mdimensions: Man (IT staff recruitment and training), Money (budget planning based on the Strategic Plan), Mate rial(infrastructure modernization and open-source software development), and Method (SOP drafting, policy formulation,and comprehensive IT strategic planning).nagement Information System (SIMRS) is a crucial strategy for improving the quality of healthcare services in the digital era. This study aims to analyze the strategy for implementing SIMRS to improve service quality at Pindad General Hospital. The method used was a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation studies. The results indicate that the implementation of SIMRS can improve the efficiency of administrative processes, accelerate access to medical information, and enhance the accuracy of patient data. However, SIMRS implementation also faces several obstacles, such as limited human resources, the need for ongoing training, and challenges in technology adaptation. Effective strategies for implementing SIMRS include improving human resource competency, strengthening technological infrastructure, and providing ongoing management support. With optimal implementation, SIMRS contributes significantly to improving the quality of healthcare services, patient satisfaction, and hospital operational performance.Keywords: SIMRS, service quality, hospital, information system, health management.